EVALUASI KEBIJAKAN LALU LINTAS TRUK BERTONASE BESAR DI KOTA PEKANBARU TAHUN 2019-2020 - Zia Zakia; Sofyan Hadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Large tonnage trucks are goods transportation that carry large amounts of industrial products such as mining, plantations, and so on. The number of trucks with large tonnage crossing the streets in Pekanbaru city is increasing every year. The large tonnage truck violates the provisions in the Pekanbaru Mayor's Decree Number 649 of 2019 concerning the Pekanbaru City Goods Transport Line. The purpose of this study is to evaluate the traffic policy of large tonnage trucks. The research method used in this study is a descriptive research method with a qualitative approach. Data collection techniques through interviews, observations, and documentation studies. The results of this study indicate that the traffic policy for large tonnage trucks based on the Mayor's Decree Number 649 of 2019 concerning the Pekanbaru City Goods Transport Line has not gone well according to its objectives, namely regarding routes and hours of traffic for large tonnage trucks when viewed from the 6 policy evaluation indicators from William Dunn, which is an indicator of the effectiveness of the traffic policy for large tonnage trucks, has not worked well, because there are still large tonnage trucks passing through city roads. Indicators of efficiency, Pekanbaru City Transportation Service, Pekanbaru Police Traffic Unit and Pekanbaru City Public Works and Spatial Planning Office have a budget in carrying out policies. The adequacy indicator has not run optimally, because the Pekanbaru City Transportation Service is rarely found monitoring large tonnage trucks at guard posts and the lack of availability of traffic signs prohibiting large tonnage trucks from passing certain roads. The equity indicator has been running well, because several large tonnage trucks that have violated have been given sanctions. The responsiveness indicator can be said to be going well, because there are people who make complaints or provide information about the existence of large tonnage trucks passing through city roads. The accuracy indicator is correct, because this policy was made to create order, security and comfort in traffic. Keywords: Effectiveness and Efficiency, Adequacy and Fairness, Responsiveness and Accuracy